1984
DOI: 10.1002/jso.2930270414
|View full text |Cite
|
Sign up to set email alerts
|

Pedunculated primary hepatocellular carcinoma

Abstract: A case report and two additional cases of pedunculated, primary hepatocellular carcinoma (PHCC) are added to those previously reviewed, and are compared with the more typical presentations of PHCC. Distinct differences include lesser associations with hepatitis B and alpha fetal protein among the pedunculated lesions. More importantly, this unique form of PHCC carries a much higher resectability rate that hopefully can be translated into longer survival in this subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…To our knowledge, this is the largest series dealing with the surgical results of pedunculated HCCs. As shown in our results, the demographics, symptomatology, physical findings, biochemical data, hepatitis disease status, and associated liver condition were similar for the P-HCC and NP-HCC groups; in contrast, Cunningham et al reported in 1984, that P-HCC had less association with hepatitis B and ␣-fetoprotein [7]. Horie et al…”
Section: Discussionsupporting
confidence: 72%
“…To our knowledge, this is the largest series dealing with the surgical results of pedunculated HCCs. As shown in our results, the demographics, symptomatology, physical findings, biochemical data, hepatitis disease status, and associated liver condition were similar for the P-HCC and NP-HCC groups; in contrast, Cunningham et al reported in 1984, that P-HCC had less association with hepatitis B and ␣-fetoprotein [7]. Horie et al…”
Section: Discussionsupporting
confidence: 72%
“…16 But, Cunningham et al reported that P-HCC is not related to hepatitis B virus infection and AFP. 17 In our case, laboratory findings including hepatitis B virus status and tumor markers were also unremarkable.…”
Section: Discussionsupporting
confidence: 48%
“…The characterization of the nature of these tumors is of primary importance for their management and treatment. Specific imaging features, such as "prominent feeding artery sign", dynamic diffuse enhancement pattern during hepatic arterial phase, and fatty components are useful for identifying the origin and nature of liver tumors [ 6 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%